Microgrid technology and engineering application - Li, Fusheng; Li, Ruisheng; Zhou, Fengquan (Academic Press, 2016)
This book is based on the authors’ research and microgrid projects since 2009, and is the most up-to-date resource on the development of microgrid technologies. In addition to basic facility and network design concepts, it covers related subjects including power supply programming and energy optimization, which means it can serve as a single volume reference to the complete microgrid system implementation.--Provided by publisher.